2005
DOI: 10.1128/aem.71.2.817-825.2005
|View full text |Cite
|
Sign up to set email alerts
|

New Thermophilic and Thermostable Esterase with Sequence Similarity to the Hormone-Sensitive Lipase Family, Cloned from a Metagenomic Library

Abstract: A gene coding for a thermostable esterase was isolated by functional screening of Escherichia coli cells that had been transformed with fosmid environmental DNA libraries constructed with metagenomes from thermal environmental samples. The gene conferring esterase activity on E. coli grown on tributyrin agar was composed of 936 bp, corresponding to 311 amino acid residues with a molecular mass of 34 kDa. The enzyme showed significant amino acid similarity (64%) to the enzyme from a hyperthermophilic archaeon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
14

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(152 citation statements)
references
References 46 publications
4
134
0
14
Order By: Relevance
“…Using this approach, several groups isolated novel enzymes from various environments (Ranjan et al, 2005;Rhee et al, 2005;Feng et al, 2007;Hardeman and Sjoling, 2007;Tirawongsaroj et al, 2008), and many of them were found to offer a good potential as new tools for industrial applications, because their biophysical properties arise from improved adaptations to the conditions met in the environment during the sampling process. Although such studies reported the characterization of metagenome-derived enzymes, insights into their physiological aspect are often lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, several groups isolated novel enzymes from various environments (Ranjan et al, 2005;Rhee et al, 2005;Feng et al, 2007;Hardeman and Sjoling, 2007;Tirawongsaroj et al, 2008), and many of them were found to offer a good potential as new tools for industrial applications, because their biophysical properties arise from improved adaptations to the conditions met in the environment during the sampling process. Although such studies reported the characterization of metagenome-derived enzymes, insights into their physiological aspect are often lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequence of the deduced protein showed only moderate identity (64.8%) to known esterases/ lipases in the database. A gene coding for a thermostable esterase (estE1) has been isolated from mud and water rich sediment of a hot water spring [95]. The enzyme showed high thermal stability and was active between 30° and 95° C. It showed 64% homology to an enzyme from a hyperthermophilic archaeon, Pyrobaculum calidifontis.…”
Section: Enzyme and Natural Productsmentioning
confidence: 99%
“…The drawback of the sequence-driven approach is overcome here, as both novel and previously described genes can be identifi ed through this method. Some genes that have been detected by virtue of functional screening are oxidoreductases [81], amylases [84], lipases [81], and esterases [95,96]. The identifi cation of clones which express benefi cial natural products or proteins fi nd direct application in the industry and emphasizes on the need of high-throughput screening technologies specifi c for required products.…”
Section: Screening Of Metagenomic Librariesmentioning
confidence: 99%
“…HSL-like carboxylesterases (EC 3.1.1.1) target ester bonds from short fatty acid chains, and their activity falls dramatically in chains longer than 8 or 10 carbons (56,57). By contrast, lipases (EC 3.1.1.3) hydrolyze ester bonds from fatty acid carbon chains with more than 10 carbons (58,59).…”
Section: Rmsd (å)mentioning
confidence: 99%